Development and characterization of oil palm (Elaeis guineensis Jacq.) empty fruit bunch and Saccharum officinarum bagasse fiber biophenolic hybrid composite insulation board - Ramlee, Nor Azlina (2022)
Recently, a high attention about concerning global warming and depletion of petrochemical based material reserves have become interest to many researchers to focus on the use of natural fibers as an alternative material for various industrial components. The abundant of biomass from natural fiber residue has attracted researchers to develop biodegradable, recyclable and eco-friendly composite to solve current environmental issue. The idea of this research is hybridizing oil palm empty fruit bunch (OPEFB) fiber and sugarcane bagasse (SCB) fiber with biophenolic resin as matrix to produce lightweight thermal insulation board for building applications. In preliminary study, the mechanical and physical properties of OPEFB and SCB single fiber were examined including the chemical composition analysis. Then, the effects of 2% silane, 4% hydrogen peroxide and combination 4% H2O2 and 2% silane (H2O2-silane) treatment on the mechanical, morphological, and structural properties of OPEFB and SCB fiber were studied with the aim to improve their compatibility with biophenolic resin. The influence of modified fibers content in composite was examined and the findings show the overall properties with 2% silane treatment were compatible with biophenolic matrix. Mechanical, structural, physical, thermal and acoustic properties of untreated and treated OPEFB:SCB fiber hybrid composite were investigated by maintaining the total fiber loading 50 wt% with different ratio of fiber applied which is 70:30 (7OPEFB:3SCB), 50:50 (5OPEFB5:5SCB) and 30:70 (3OPEFB:3SCB). For untreated composite analysis, 7OPEFB:3SCB hybrid composite display highest tensile strength and modulus, 5.56 MPa and 661.MPa respectively, 3OPEFB:7SCB hybrid composite show lower water absorption and thickness swelling, 5OPEFB:5SCB hybrid composite displayed better thermal stability with residue 45.04% and low thermal conductivity, 0.0863 W/mK, and in acoustic view untreated pure SCB composite has capability to conduct high frequency range, 3200Hz. The characterization of treatment composite show hybrid composite with 2% silane treatment and ratio 70:30 shows the highest improvement on tensile strength (11.67 MPa) and modulus (935.12 MPa). Hybridization both fiber with silane treatment (ST), ST 5OPEFB:5SCB show highest flexural strength (16.82MPa) and compression strength (6.527 MPa) in comparison with 4% v/v hydrogen peroxide treated composite. TGA result shows hydrogen peroxide treatment (HT), HT 5OPEFB:5SCB was effective in thermal stability with 58% of residue at 500°C while silane treated, ST 5OPEFB:5SCB perform well in thermal conductivity analysis with 0.0542 W/mk. Sound absorption coefficient (α) was carried out according to ISO 10534-2:2001, and perform silane treatment; ST 5OPEFB:5SCB better to conduct up to 4250Hz with no air gap distance. The sound absorption coefficient were shifted to the left when the air gap applied. Morphological properties of the samples were carried using scanning electron microscopy (SEM) to observed fracture behavior and fiber pull out of the tensile fracture samples. Density, void content, water absorption and thickness swelling of the composite were also determine in this study. Based on the preliminary study, hybrid composite of silane treated fiber with ratio 50:50; ST 5OPEFB:5SCB presents excellent in overall properties among the others hybrid composite. In overall, the improvement of oil palm empty fruit bunch and sugarcane bagasse fiber behavior in natural fiber reinforced composite has great concern in advanced material building development. The characterization of biophenolic hybrid composite of ST 5OPEFB:5SCB has potentially effective as wall thermal insulation in building sector and future prospective usage.